Fikih Wanita dan Pemahaman Remaja Putri di Pondok Pesantren Sunan Drajat - Kustina, Fariha (Multidisciplinary Journal of Education , Economic and Culture, 2023)
Physical changes in both appearance and body proportions are one of the characteristics of puberty. For young women, it is usually marked by menstruation. The purpose of this study is to provide an understanding through deepening the study of women's jurisprudence so that young women truly understand menstruation, childbirth, istihadah and matters related to women's affairs. Qualitative methods with approaches to respondents have opened space for researchers to reveal problems and solutions for respondents. The research population was female students of the Sunan Drajat Islamic Boarding School who were studying at Paciran 2 Public Middle School. The results of the research have opened up perceptions and understanding for Paciran 2 Public Middle School students in understanding and practicing how to purify from menstruation, childbirth, istihadah and how to carry out worship properly in accordance with sharia.